I Bring Home My Used Menstrual Pad: Water, Sanitation, Hygiene, and Menstrual Hygiene Management in Middle Schools with Limited Sanitation Access - Ni Putu Gita Saraswati Palgunadi; I Gede Astra Wesnawa; I Ketut Sudiana (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Menstruation is a critical aspect of puberty for adolescent girls, and effective Menstrual Hygiene Management (MHM) is vital for their health and well-being. In many schools in Indonesia, however, limited access to Water, Sanitation, and Hygiene (WASH) facilities creates significant barriers to proper MHM. This study aims to explore the challenges faced by adolescent girls in managing menstrual hygiene in schools with inadequate sanitation. A Participatory Action Research (PAR) approach was employed using the photovoice method, allowing 20 female students from SMPN 3 Selemadeg Timur, a school in Bali, to document their experiences with MHM. Data were collectedthrough interviews, Focus Group Discussions, and thematic analysis of the photographs. The findings revealed that inadequate toilets, lack of privacy, poor water supply, and ineffective waste management systems significantly hindered students' ability to manage menstrual hygiene at school. As a result, many students adopted the practice of taking home used menstrual pads due to the absence of proper disposal facilities. Cultural taboos and fear of bullying further complicated the issue, preventing students from reporting sanitation problems. Barriers to improving these conditions included limited funds, low awareness of cleanliness, and low prioritization of sanitation within the school. These factors led students to normalize taking used pads home or leaving school to change pads as an adaptation to the unsatisfactory sanitation conditions. The study highlights the need for improved sanitation infrastructure, better waste management, and a more supportive school environment for managing menstrual hygiene.